2015
DOI: 10.1108/ijhcqa-07-2013-0092
|View full text |Cite
|
Sign up to set email alerts
|

Food production and service in UK hospitals

Abstract: The paper provides a theoretical basis for process enhancement of hospital food production and the provision of high-quality hospital food.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 36 publications
1
19
0
3
Order By: Relevance
“…Among those studies that included only current state mapping, four reported an associated lead time (Darlington and Rahimifard, 2006;Lehtinen and Torkko, 2005;Taylor, 2006b;Vlachos, 2015), one cycle time (Simons et al, 2003) while four studies reported none (Ahmed et al, 2015;Francis et al, 2008;Kennedy et al, 2013;Melvin and Baglee, 2008).…”
Section: Application Of Vsm Additional Lean Tools and Performance Inmentioning
confidence: 99%
See 4 more Smart Citations
“…Among those studies that included only current state mapping, four reported an associated lead time (Darlington and Rahimifard, 2006;Lehtinen and Torkko, 2005;Taylor, 2006b;Vlachos, 2015), one cycle time (Simons et al, 2003) while four studies reported none (Ahmed et al, 2015;Francis et al, 2008;Kennedy et al, 2013;Melvin and Baglee, 2008).…”
Section: Application Of Vsm Additional Lean Tools and Performance Inmentioning
confidence: 99%
“…Although state maps were in general graphically illustrated, two additional studies (Engelund et al, 2009;Sathiyabama and Dasan, 2013) only described the current and future states. There were six studies (Ahmed et al, 2015;Darlington and Rahimifard, 2006;Kennedy et al, 2013;Lehtinen and Torkko, 2005;Melvin and Baglee, 2008;Vlachos, 2015) that only used the current state map and one study (Noorwali, 2013) that gave a description of the current situation at a single plant level, against three studies (Francis et al, 2008;Simons et al, 2003;Taylor, 2006b) at a supply chain level.…”
Section: Application Of Vsm Additional Lean Tools and Performance Inmentioning
confidence: 99%
See 3 more Smart Citations